Aspectos genéticos da actividade física. Estado actual do conhecimento baseado nos modelos animal e humano com amostras gemelares - Maria Madalena Castro Oliveira; José Antônio Ribeiro Maia (Universidade Federal do Rio Grande do Sul, 2002)
Physical activity is a behaviour associatedto quality oflife andlongevity. This phenotype presents variation at the population levei whose main determinants studiedare, essentially, socio-economic, demographic and psychological. Yet, expkined variance of thes determinants is very low(<30%). A mainpart of the total variance of this phenotype has to be associated with another fundamental agent -the phenotype. The work we are presenting wants to review, in an exhaustive way, animal and human research with the twin methodology. Main research has dealt with three different expressions ofthe phenotype physical activity - total physical activity, sports participation andenergy expenditure. From the results emerges clearly the importance of genetic feature in the interindividual variation of physical activity at the population levei, whosemain effect centres around 50 -70%.